Studying identification and cultivation Macrocybe titans, a new record species for Vietnam collecting in Cat Tien National Park south of Vietnam - Duong, Pham Ngoc; Duy, Vu Dinh; Anh, Nguyen Thi; Tuyet Xuan, Bui Thi; Tham, Le Xuan (Academia Journal of Biology, 2017)
Seven species of Genus Macrocybe Pegler have been recorded in the world. These include: Macrocybe crassa, M. gigantean, M. lobayensis, M. pachymeres, M. praegrandis, M. spectabilis, M. titans. Most of species in this genus are edible; culture technology for some species such as M. crassa and M. gigantean have been studied. In Vietnam only two species, M. crassa and M. gigantean, have been recorded, but not much studies have been done on this genus especialy on cultivation. In this study we describe the third species of this genus, M. titans, in Viet Nam which was collected in Cat Tien National Park, the world natural biosphere reserve in Vietnam. We also study about cultivation of this species in labortary of fungi in Cat Tien National Park. Our researches in morphology showed that specimens collected in Cat tien National park are similar with Pegler about description of M. titans. Our molecular biology analyze at gene 28S-ribosomal RNA also showed that sequence of speciments collected in Cat Tien National Park have hight similar to the sequence of other species in genus Macrocybe Pegler. from Genbank. Our cultivation researchs also show that mycelium of M. titans can grows very well in PGA medium including potato, glucose, and agar. We found the best recipes of medium for fruitbody cultivation: sawdust,straw and added nutrient. This result gives a good opportunitite for commercial culture this species in Viet Nam.   Citation: Pham Ngoc Duong, Vu Dinh Duy, Nguyen Thi Anh, Bui Thi Tuyet Xuan, Le Xuan Tham, 2017. Studying identification and cultivation Macrocybe titans, a new record species for viet nam collecting in cat tien national park south of vietnam. Tap chi Sinh hoc, 39(2): 185-194. DOI: 10.15625/0866-7160/v39n2.8367 *Corresponding author: netnhatrang2001@yahoo.com; duydinhvu87@gmail.com Received 2 June 2016, accepted 20 March 2017